Investigating life history and predation defense costs associated with emamectin benzoate resistance in Spodoptera frugiperda (Lepidoptera: Noctuidae) - Muraro, Dionei S.; Guidolin, Aline S.; Cruz, João V.S.; Malaquias, José Bruno [UNESP]; Bernardi, Oderlei; Omoto, Celso (Elsevier, 2024)
Evidence of field-evolved resistance to emamectin benzoate has already been reported in Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) in Brazil. To investigate the fitness costs associated with emamectin benzoate resistance, we used an F2 screen to select resistant (Ben-R) and susceptible (Ben-S) strains of S. frugiperda from a field-collected population in Mato Grosso State, Brazil. Fitness costs were quantified by comparing biological (life history traits) and behavioral (ability to escape from predation by Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae)) parameters of Ben-R, Ben-S, and heterozygote strains reared on non-Bt maize and artificial diet. The resistance ratio of S. frugiperda resistance to emamectin benzoate was ∼ 2445-fold. Based on life table parameters, Ben-R and heterozygote strains had a higher mean generation time (T) than Ben-S strain on both food sources. The intrinsic rate of population increase (rm) of Ben-R strain was ∼ 35% lower than Ben-S and heterozygote strains. In contrast, there was no significant difference in predation rate of 3rd instar larvae of Ben-R, Ben-S and heterozygote strains by P. nigrispinus. Our findings suggest the presence of strong fitness costs associated with emamectin benzoate resistance in S. frugiperda, as evidenced by life history traits. Conversely, no fitness costs were linked to the defensive response against predation by P. nigrispinus.
Keywords: Fall armyworm; Fitness costs; Podisus nigrispinus; Resistance